Serum CPK and Hypoxic-Ischemic Encephalopathy (HIE) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The value of brain-typical creatine phosphokinase iso-enzyme (CPK-BB) determinations in the assessment of brain damage due to neonatal asphyxia in 33 full-term infants has been assessed in the Services of Neonatology, Child Neurology and Radiology, Clinica Infantil, Cindad Sanitaria "La Paz", Madrid, Spain.